The Lipo-DIEP Flap Breast Reconstruction: A Valuable Innovation for Maximizing Abdominal Tissue Volume - Benedetto Longo, MD, PhD; Gennaro D’Orsi, MD; Alessio Farcomeni, PhD; Martina Giacalone, MD; Elettra Gagliano; Lisa Vannucchi, MD; Maximilian Catenacci, MD; Gianluca Vanni, MD; Claudio Oreste Buonomo, MD; Valerio Cervelli, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. The deep inferior epigastric perforator (DIEP) flap is universally considered the gold standard technique for breast reconstruction (BR), though it cannot always be proposed to patients with insufficient donor-site volume. We explore the efficacy of autologous fat transfer (AFT) of the Holm abdomen zone IV in the retropectoral plane during DIEP flap reconstruction (lipo-DIEP flap), to enhance the volume provided by the abdominal donor site in patients with low body mass index (BMI). Methods:. We prospectively enrolled patients with BMI less than 25 kg/m2 and candidates for lipo-DIEP flap BR (group A) comparing them with a control group (group B) undergoing traditional DIEP flap BR with the same characteristics of the first group (BMI < 25 kg/m2). Patients belonging to group A underwent magnetic resonance imaging preoperatively and 6 months after the BR, evaluating the adipose tissue volume retained in the retropectoral space. Results:. A total of 40 breasts were included in the study. The 2 groups were homogeneous regarding the collected variables, except for mean delayed AFT sessions (0.25 versus 0.95; P= 0.00094). The average volume of retropectoral AFT was 116.25 mL (SD 31.36). Six months after the procedure, the mean retropectoral fat volume calculated through magnetic resonance imaging was 48.64 mL (SD 14.15), whereas the mean graft integration rate was 45.98% (range, 30.7%–64.2%). Conclusions:. The lipo-DIEP flap is a valuable technique for patients with insufficient donor-site volume. Immediate retropectoral fat grafting from the Holm zone IV has proven to be safe in terms of complications, reducing the need for further AFT sessions.